Effect of gender and apolipoprotein E genotype on response to anticholinesterase therapy in Alzheimer's disease. - MacGowan, S; Wilcock, G; Scott, M (1998)
BACKGROUND: Anticholinesterase therapies offer modest benefit to subgroups of AD sufferers. However, there has previously been no way of predicting which patients will respond to any of the drugs. OBJECTIVE: To discover if gender and/or apolipoprotein E genotype can be used as predictors of response in the clinical setting. DESIGN: 107 patients from the Bristol Memory Disorders Clinic took part in a double-blinded or open label trial of tacrine therapy for between 3 and 12 months or an open label trial of galanthamine therapy for 3 months. RESULTS: After 3 months of therapy, gender was found to be the only significant influence on the number of responders to anticholinesterase therapy. Men had a 73% greater chance of responding than women (p = 0.012). While ApoE genotype did not modify response to therapy in the short term, there are indications that it may affect response over the longer term (up to 12 months), and also that the initial advantage of male gender may not be maintained after 3 months. CONCLUSION: Gender is likely to be a more powerful determinant of outcome of anticholinesterase treatment than apolipoprotein E status in the short term.